Effects of different aeration strategies on removal of organics, nitrogen and phosphorus in sequencing batch biofilm reactor (SBBR): Performance, microbial community and nitrogen cycling pathways. (October 2022) - Zhu, Wentao; Zhang, Xuehui; Yuan, Sicheng; Sang, Wenjiao; Tang, Xinhua; Zhang, Shiyang
Abstract: Aquaculture usually produces a large amount of wastewater posing a serious threat to the receiving water environment. In this study, five morphologically identical sequencing batch biofilm reactors (SBBR) were established to treat simulated tilapia aquaculture wastewater under different aeration strategies, involving two dissolved oxygen (DO) concentrations (2 or 3 mg/L) and five aeration/non-aeration ratios (ANRs: 1 h/5 h, 2 h/4 h, 3 h/3 h, 4 h/2 h, 5 h/1 h). The nutrients under the different aeration strategies were mainly removed by simultaneous nitrification, denitrification and phosphorus removal (SNDPR), which was prone to occur under high DO conditions. High DO concentration and appropriate ANR were beneficial to phosphorus removal. High-throughput sequencing analysis revealed that the increase of DO or ANR favored the enrichment of Patescibacteria, but decreased the relative abundance of Proteobacteria. In addition, the relative abundance of nitrification functional genes ( amoABC, hao, and nxrAB ) responsible for nitrogen conversion was low, which was a critical and limiting factor in the nitrogen cycle. The SBBR achieved the highest performance at the ANR of 4/2 and DO of 3 mg/L. Graphical abstract: Unlabelled Image Highlights: Nitrogen was mainly removed by SND under different aeration/non-aerations. Phosphorus was more easily removed at moderately increased ANRs. SNDPR was more likely to occur under high DO concentration (DO = 3 mg/L). amoABC, hao, and nxrAB were the key and limiting factors in the nitrogen cycle. The adverse effects of DNRA/ANRA could be reduced by increasing DO concentration.